The Development Of Light Emitting Diode (Led)-Based As A Baby-Friendly Device For Treatment Of Neonatal Jaundice - Zainudin, Nadira Syuhada (2018)
Sixty percent of newborns are jaundiced in their first two weeks oflife for their liver is immature and unable to cope with the production of bilirubin. Phototherapy treatment is proven and widely known to treat hyperbilirubinemia. The common light sources used in conventional phototherapy device are special blue fluorescent tubes, compact fluorescent tubes (CFT), halogen spotlights and fibre optic blankets. However, the conventional device is capacious, expensive and cost involved in periodical maintenance. Hence, the idea ofBiliBaju which based on LED is to develop a low cost, mobile, and baby-fiiendly phototherapy device, and promising the same or better effectiveness in treating neonatal jaundiced.